Investment intention on Private Retirement Scheme (PRS) among small business owners and self-employed individual - Ramin, Ahmad Kaseri; Zabri, Shafie M.; Md Diah, Mohd Lizam; Ahmad, Abd Razak; Mohd Safian, Edie Ezwan (Journal of Advanced Research in Dynamical & Control Systems, 2018)
Private retirement planning scheme (PRS) was first introduced in 2012 in support to private sector employees to prepare for their retirement. The PRS is a retirement scheme introduced by the Private Pension Administrator (PPA) in addressing the inadequacy of retiree’s savings in meeting their retirement needs to accommodate the increasing life expectancy and rising living standards and insufficient fund to support life after retirement. This study aims to gauge the level of investment intention among small business owners and selfemployed individual on PRS scheme. Total 341 respondents involved in the study in which data was gathered through questionnaires. The study found that level of investment intention on PRS was relatively mediocre. Respondent knowledge, PRS product literacy and economic condition were found to have an influence on PRS investment intention.